2005
DOI: 10.5254/1.3547872
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Property Relationship of a Thermoplastic Vulcanizate (Tpv)/Layered Silicate Nanocomposites Prepared Using Maleic Anhydride Modified Polypropylene as a Compatibilizer

Abstract: Thermoplastic vulcanizate(TPV)/organoclay nanocomposites have been successfully prepared by melt intercalation method. Maleic anhydride modified polypropylene has been used as a compatibilizer. The TPV/organoclay nanocomposites have been characterized by Fourier-transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD) and Transmission Electron Microscope (TEM). The nanocomposite as evidenced by X-ray diffraction is an intercalated one. The nanocomposites exhibited remarkable improvement in tensile and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Currently, maleic anhydride-modified polypropylene is being studied and widely used [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, maleic anhydride-modified polypropylene is being studied and widely used [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Different kinds of nanofiller have been used to prepare nanocomposites like nanoclay, spherical nanoparticles, carbon nanotube, among others (58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72). In addition, the development of environment-friendly polymers is one of recent important issues.…”
Section: Applications Of Pp/epdm Blendsmentioning
confidence: 99%
“…Studies on TPV/clay nanocomposites (TPVCN) have been widely reported in literature . Nanostructured TPVCN can be fabricated by melt mixing method using proper modification of nanofillers and matrix polymers to impart sufficient thermodynamic compatibility between them.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, TPVCN is successfully employed in diverse applications such as electrical, construction, healthcare, packaging, and many more fields. The literature review revealed that some published papers are dedicated to the polypropylene/ethylene propylene diene monomer rubber (PP/EPDM), and ethylene vinyl acetate/natural rubber ((EVA/NR) blends based TPVCN.…”
Section: Introductionmentioning
confidence: 99%